The Transformation of Jakarta's Administrative Status, 1905-1964: From Gemeente Batavia to Special Capital Region - Tomy Wijaya; Syafruddin Yusuf (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study examines the historical progression of Jakarta's administrative classification from Gemeente Batavia (1905) to the Special Capital Region (DKI) in 1964. This study analyzes the impact of colonial heritage, the Japanese occupation, and post-independence political dynamics on Jakarta's evolution from a colonial city to a national capital with a unique administrative identity. The employed methodology is the historical method, which includes the stages of heuristics, source criticism, interpretation, and historiography. This study uses a historical institutionalism framework to analyze the continuity and institutional transformation (path dependency) within Jakarta's government. The study's findings reveal that the Gemeente Batavia period (1905-1942) instituted a modern municipal governance framework under colonial supervision; the Japanese occupation (1942-1945) intensified centralization and solidified the identity of "Jakarta"; while the post-independence era (1945-1964) illustrated the Republic's efforts in political consolidation through administrative reforms. Law No. 101964, which established the Special Capital Region of Jakarta, served both as an administrative measure and a political assertion of Indonesia's national identity and modernity. This research elucidates urban political and institutional history by illustrating that the Jakarta governance model encapsulates the amalgamation of colonial heritage, centralized power, and nation-building ideology in postcolonial Indonesia.